Magnetic Nanoparticles Based Solid Phase Extraction Methods for the Determination of Trace Elements - Ozturk Er, Elif; Dalgic Bozyigit, Gamze; Buyukpinar, Cagdas; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2022)
The past three decades has seen significant advancements in instrumental detection techniques for both organic and inorganic analytes, leading to more accurate and precise measurements. The relevance of sample preparation prior to instrumental reading cannot be underestimated, and this area has also seen major improvements, with solid phase extraction (SPE) and its miniaturized version (solid phase microextraction, SPME) serving as an efficient clean-up and preconcentration method for analytes. Magnetic nanoparticles (MNPs) belong to the new generation of sorbents, and their characteristic small size and easy manipulation under magnetic field make them ideal materials for extraction of several analytes. This review presents the basic principles of SPE and SPME, and lays more emphasis on different types of MNPs that have been used as efficient separation and preconcentration tools. In addition, application of MNPs for the determination of trace elements in environmental, biological and food samples are well documented in this review.
Keywords: Magnetic nanoparticles (MNPs); solid phase extraction (SPE); solid phase microextraction (SPME); trace elements; IRON-OXIDE NANOPARTICLES; PLASMA-MASS SPECTROMETRY; CORE-SHELL NANOPARTICLES; COATED FE3O4 NANOPARTICLES; BIOLOGICAL SAMPLES PRIOR; ION-IMPRINTED POLYMER; ATOMIC-ABSORPTION-SPECTROMETRY; SODIUM DODECYL-SULFATE; ENVIRONMENTAL WATER; HEAVY-METALS; Chemistry